ISOLATION AND IDENTIFICATION BACTERIA OF CLINICAL MASTITIS ON ETTAWAH CROSSBRED GOAT - Widodo Suwito; A.E.T.H. Wahyuni; Widagdo Sri Nugroho; Bambang Sumiarto (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2013)
ABSTACT Ettawah crossbred goat (PE) IS much more usefull to milk goat produce. One of constraints in milk goat is clinical mastitis. Clinical mastitis is economic inflict a financial lost because stopped of milk production, high cost of treatment, and even cause death. The aim of the present study was to determine the kind bacteria that can cause clinical mastitis in PE. A total of 13 clinical mastitis milk and water used to wash the six udder samples were collected from dairy PE farms. All samples were subjected for isolation and identification of bacteria based on biochemical reactions. From the clinical mastitis milk samples, bacteria isolated were Staphylococcus aureus (55.55%), Pseudomonas sp (27.77%), Streptococcus sp (8.3%) and Bacillus sp (8.33%). Whereas, Pseudomonas sp (77.77%) and Bacillus sp (22.23%) were isolated from the water used to wash the udder. The study showed that more clinical mastitis in PE caused by Staphylococcus aureus. Water use to wash the udder was source of Pseudomonas sp causing clinical mastitis in PE.